Rancangan Sistem Informasi Penyewaan Kamar Kos Pada Rumah Singgah Jerry - dewi leyla; Een Juhriah (CV. Syntax Corporation Indonesia, 2023)
This research aims to facilitate employees in data processing at Boarding Room Rentals at Jerry Bogor Halfway House, resulting in precise and accurate data. The system is made with the Research &Development (R&D) method which a research method based on facts, bservations, library research and data analysis. The system is built using the desktop-based Java programming language and MySQL based data storage. The results of this research is the existence of a new system that can facilitate and help employees’ performance especially in the front office in carrying out their tasks optimally, no mistakes and can facilitate employees to process the data bookings, rentals, and payments stored in the database.